Optimal Composition Ratio Achieves Maximum Compressive Strength in Sandwich Panels: Rasio Komposisi Optimal Menghasilkan Kekuatan Tekan Maksimal pada Panel Sandwich - Hardiyanto, Dimas; Tjahjanti, Prantasi Harmi (Indonesian Journal of Innovation Studies, 2025)
General Background: Sandwich panels are widely used in construction due to their lightweight structure and functional efficiency, making material strength a critical factor in performance. Specific Background: Defects such as bubbles and uneven surfaces in sandwich panels often reduce product quality and are related to bonding issues between layers. Knowledge Gap: Limited studies specifically examine how variations in polyol and isocyanate composition affect compressive strength in repaired sandwich panels. Aims: This study aims to analyze the effect of composition ratios of polyol and isocyanate on the compressive strength of sandwich panels. Results: Experimental testing shows that the 70:30 composition produces the highest compressive strength of 1.13 MPa, compared to 0.513 MPa for 50:50 and 0.696 MPa for 60:40. Novelty: The study provides experimental evidence of optimal composition ratio for improving bonding performance in sandwich panel repair. Implications: The findings offer a reference for selecting material composition to improve the strength and quality of sandwich panels in industrial applications. Keywords: Sandwich Panel, Polyurethane, Isocyanate, Compressive Strength, Material Composition Key Findings Highlights Highest strength achieved at specific material proportion Measured values vary significantly across tested ratios Experimental data confirm sensitivity to composition changes